A Perceptual Evaluation of Individual and Non-Individual HRTFs: A Case Study of the SADIE II Database - Cal Armstrong; Lewis Thresh; Damian Murphy; Gavin Kearney (Applied Sciences, 2018)
As binaural audio continues to permeate immersive technologies, it is vital to develop a detailed understanding of the perceptual relevance of HRTFs. Previous research has explored the benefit of individual HRTFs with respect to localisation. However, localisation is only one metric with which it is possible to rate spatial audio. This paper evaluates the perceived timbral and spatial characteristics of both individual and non-individual HRTFs and compares the results to overall preference. To that end, the measurement and evaluation of a high-resolution multi-environment binaural Impulse Response database is presented for 20 subjects, including the KU100 and KEMAR binaural mannequins. Post-processing techniques, including low frequency compensation and diffuse field equalisation are discussed in relation to the 8802 unique HRTFs measured for each mannequin and 2818/2114 HRTFs measured for each human. Listening test results indicate that particular HRTF sets are preferred more generally by subjects over their own individual measurements.